Don’t Fight the Fed! - Maio, Paulo (Review of Finance, 2014)
Abstract Monetary policy, as captured by changes in the Fed funds rate (FFR), is a useful signal for investors. I analyze the economic significance of trading strategies based on the “out-of-sample” forecasting power of FFR for excess equity returns. A simple market-timing strategy produces an annual Sharpe ratio of 0.55 and a certainty equivalent return (CER) gain of 3.37% per year, whereas a buy-hold strategy has a Sharpe ratio of 0.41. Rotation trading strategies for portfolios sorted on size, book-to-market, and momentum have a Sharpe ratio and CER gain as high as 0.73 and 9.60% per year, respectively. Dynamic strategies for other asset classes also produce economically significant gains. Generally, the strategies based on FFR outperform those associated with alternative predictors.